(untitled) (Marketing Journal, 2026)
Abstract This article examines the theoretical and methodological foundations for improving efficiency in textile industry enterprises based on the Balanced Scorecard (BSC). The BSC is considered as a strategic management tool that integrates financial and non-financial aspects of enterprise activity into a unified management system. The study substantiates the possibilities of performance evaluation based on the interrelation between customer relations, internal business processes, innovation development, and financial results. It is concluded that the implementation of the BSC in textile enterprises contributes to the improvement of management processes, efficient resource utilization, and enhanced competitiveness. Keywords: Balanced Scorecard, textile industry, strategic management, efficiency, financial and non-financial indicators, innovation development, internal business processes, competitiveness.